A Bibliometric Analysis of Free Open-Source Software Adoption (2001-2023) - Silva, Domingos G.; Coutinho, C.; Costa, C. J. (Procedia Computer Science, 2025)
Free and open-source software (FOSS) has gained increasing relevance worldwide due to its potential to catalyze innovation, reduce costs, and promote technological independence, among other benefits. Although widely adopted in developed countries, developing nations are beginning to realize its transformative potential in socioeconomic development and digital inclusion. Therefore, understanding the evolution of FOSS adoption and its impact is crucial. This research performed a bibliometric analysis of FOSS adoption from 2001 to 2023, using citation and reference data from scientific articles published in high-impact journals. The analysis was conducted using the VOSviewer software, and the data were collected from the Scopus platform. The research revealed a significant growth in scientific production on FOSS, with the United States, the United Kingdom, and India being the countries that produced the most research on the subject. The most common research topics were "foss," "health," "cost," and "information systems". Additionally, there was a lack of approach to the theme of interoperability in countries that collaborate less. The study provides a comprehensive view of the current state of research on FOSS adoption and its impact on different areas. It highlights the importance of understanding the evolving nature of FOSS adoption and its impact in various countries, which could aid researchers, managers, and decision-makers in developing effective strategies. Finally, it emphasizes the potential of FOSS adoption in developing and low-income countries as a viable economic alternative for adopting information and communication technologies.